Late Pleistocene proboscidean population dynamics in the North American Midcontinent. (17th February 2017) - Widga, Chris; Lengyel, Stacey N.; Saunders, Jeffrey; Hodgins, Gregory; Walker, J. Douglas; Wanamaker, Alan D.
Abstract : Understanding megafaunal population dynamics is critical to testing and refining scenarios of how extinctions occurred during the terminal Pleistocene. Large‐scale, collections‐based, chronological and taphonomic analyses of midwestern Proboscidea suggest divergent population histories in mammoths and mastodons after the Last Glacial Maximum (LGM). Although extinction of both taxa occurred in the very late Bølling‐Allerød (B‐A) or early Younger Dryas (YD), Mammuthus is dominant during the LGM with a decreasing presence in the region until extirpation. Mammut americanum however, is absent during the LGM but becomes the dominant taxon during the subsequent B‐A. Trace and physical evidence of large carnivores in post‐LGM proboscidean assemblages is extremely rare, suggesting apex predators had minimal impact on mammoth and mastodon populations at this time. The ultimate mechanism(s) of extinction remain unclear; however, the wide geographical distribution of late Mammut and an increase in the frequency of multi‐animal death assemblages is consistent with a large, destabilized population experiencing periodic boom‐bust cycling at the end of the B‐A. We suggest this pattern is due to the collapse of trophic controls on proboscidean populations prior to the LGM and a subsequent system‐wide shift from top‐down to bottom‐up regulatory mechanisms in Proboscidea.